Indomie Product Marketing Strategy in Entering International Marketing: Indomie Product Marketing Strategy In Entering International Marketing - Wildan Izzaty; Nuri Aslami (Journal Of Social Research, 2021)
The company needs to prepare a strategy to market its products in order to penetrate the international market. Market competition is so much a challenge for entrepreneurs. In this case, one of the companies that is able to survive with intense competition and successfully penetrate the international market is PT. Indofood Makmur is a company engaged in food and beverage processing. The brand name used by PT Indofood CBP Sukses Makmur Tbk, is Indomie. first time comes with Chicken Broth Flavor only. In Indonesia, the term "Indomie" is commonly used as a generic term that refers to instant noodles. This study aims to describe the marketing strategy used by Indomie products in entering international marketing. In this research, the writer uses descriptive qualitative method where the data collection technique used is literature study. The results showed that the strategy used by Indomie products to enter the international market was by implementing the 3A strategy, namely Acceptability (Product), Availability (Place), and Affordability (Price). With the distinctive taste of the archipelago spread throughout Indonesia, Indomie has been recognized by consumers that Indomie is an original product from Indonesia.